O desafio na contratação e elaboração de projetos para execução de obras rodoviárias: 'o fator projeto' - Cordeiro, Alexandre Zananiri (2014)
In 2007 the Brazilian Government established PAC – the growth acceleration program, a set of infrastructure projects in which the DNIT occupies a prominent position, with volume of resources over R$ 58 billion. Since the start of the program the main obstacle is the lack of quality projects. Engineering projects are a crucial step to launch bids for infrastructure works. This project bottleneck, associated with the bidding process, is called 'project factor'. In 2011 was instituted the RDC – Differentiated Contract Regime, in order to remove these obstacles. This work arises from the need of the Secretariat of monitoring the growth acceleration program, linked to the Ministry of Planning, and of the National Department of Transport Infrastructure, linked to the Ministry of Transport, to understand the challenges posed by the 'project factor' in the implementation of projects related to road work under PAC. To this end, we analyzed aspects of contracting by the public administration, emphasizing changes in the bidding process after the Differentiated Contract Regime (RDC) and the contemporary forms of pre-contractual relationships, addressing public private partnerships (PPP), expressions of interest of private initiative (PMI) and competitive dialogue. After a presentation of the DNIT and the process of institutionalization of RDC within the agency we concluded that three aspects have contributed to minimize the effects of 'project factor': the first, procedural in nature, is directly related to the effect of the implementation of the new tendering scheme. In complex projects, such as those in the area of infrastructure, the development of pre-contractual relations bring considerable gains. Procedures to promote the reduction of information asymmetries and the stoning of the object to be hired, as, for example, the Competitive dialogues, bring considerable gains for both public administration and private entity. The second aspect is related to the nature of the DNIT. It is a agency with accumulation of knowledge in engineering and project management. By adopting intensely RDC, showed installed capacity and advanced monitoring parameters and risk management and generated a current and appropriate regulatory set to face the challenges of the new regime of contractions. The third aspect is also related to the institutional aspect of the DNIT. This is its organizational structure, which influences the bidding processes and governance and combines two predicates: security in accountability amongst the Directors-members when they share a decision, and safeguarding of technical staff. These three aspects have led to greater efficiency and effectiveness of Autarchy and minimized the 'project factor'. DNIT management report of 2012 quotes that in RDC there is a reduction of up to 50% at the time of the bidding process in relation to competition and price-taking modes. The implementation of the Electronic RDC, which allows participation of companies from all over the country, increased competitiveness and helped to execute $ 10.2 billion in works and services in transport infrastructure.